Neuroprotective nature of adipokine resistin in the early stages of focal cerebral ischemia in a stroke mouse model. (March 2018) - Behrouzifar, Sedigheh; Vakili, Abedin; Bandegi, Ahmad Reza; Kokhaei, Parviz
Abstract: New evidence suggests that resistin may have a therapeutic potential effect in management of neurodegenerative disease; but its role in the pathophysiology of stroke-induced injuries is not understood. However, further investigations are required to elucidate the effect of resistin and explore its possible molecular mechanisms on the ischemic reperfusion injury. Transient focal cerebral ischemia was induced by the middle cerebral artery occlusion (MCAO) in mice. Animal treated with resistin at doses of 25, 50, 100, 200, and 400 ng/mouse, on the MCAO commencement. Neurological function, infarct size, brain edema and Blood-brain barrier (BBB) disruption were measured. Additionally, content of malondialdehyde (MDA), TUNEL-positive cells and apoptosis-related proteins were assessed by immunohistochemistry and western blot techniques. Resistin mRNA was detected at 3 h, 6 h, 12 h and 24 h after MCAO using real-time QRT-PCR method. Central administration of resistin only at doses of 200 and 400 ng/mouse considerably reduced the infarct size and promoted neurological function (p < 0.001). In addition, resistin (400 ng/mouse) significantly decreased brain edema (p < 0.001), evans blue (EB) leakage (p < 0.05), MDA content (p < 0.005), apoptotic cells and apoptosis-related proteins (p < 0.001). Resistin mRNA expression markedly increased at 12-h time point and then returned to basal level at 24 h after MCAO. Our findings revealed that treatment with resistin could attenuate ischemic damage in a dose-dependent approach via suppressing apoptosis and oxidative stress. Application of resistin in clinical settings to treat stroke and brain ischemia warrants further research. Highlights: Ischemic stroke induced cerebral ischemic damage, blood brain barrier disruption and edema formation. Treatment with resistin reduced ischemic damage, blood brain barrier disruption and brain edema in a dose-dependent approach. Via suppressing apoptosis-related proteins caspase-3 and caspase-8 and oxidative stress. >Application of resistin in clinical settings to treat stroke and brain ischemia warrants further research.